Sosialisasi Literasi Politik Bagi Pemilih Pemula Terhadap Konsep Demokrasi Dan Otoritarianisme - Wasisto, Muhammad Adiz; Wahyuningratna, Ratu Nadya (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Democracy and authoritarianism represent two contrasting systems of governance. Since the Reform Era and the fall of President Soeharto’s New Order regime, public discourse in Indonesia has consistently focused on strengthening democratic values and preventing the resurgence of authoritarian practices. Despite the progress made, Indonesia is still regarded as a democracy in development, with several persistent issues undermining its democratic framework. These challenges include widespread corruption, the repression and criminalization of political opposition, limited judicial independence, socioeconomic disparities, and the exploitation of identity politics, issues that have continued into President Joko Widodo’s second term. In light of these concerns, this educational outreach program has been designed. It targets eleventh-grade students, who represent a group of first-time voters in the upcoming election. The goal is to provide these students with the critical skills needed to assess the policy platforms of electoral candidates. The program will be delivered through a combination of lectures, interactive discussions, and post-session assessments. The intended outcome is to enhance students’ awareness of the significance of democratic values, encourage resistance to authoritarian tendencies, and promote informed, principle-based voting behavior.